The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1007/s10646-013-1086-5
|View full text |Cite
|
Sign up to set email alerts
|

Why mammals more susceptible to the hepatotoxic microcystins than fish: evidences from plasma and albumin protein binding through equilibrium dialysis

Abstract: To elucidate the interspecies variation of susceptibility to microcystins (MCs), fresh plasma and purified albumin from six kinds of mammals and fish were used in toxins-substances binding test. Protein contents in the test plasma were analyzed and the binding characteristics to MCs were compared. Two kinds of widely observed MCs, microcystin-LR (MC-LR) and microcystin-RR (MC-RR) were tested and data were collected through the method of equilibrium dialysis. It was found that total plasma protein and albumin c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 45 publications
0
11
1
Order By: Relevance
“…The persistent, measureable levels of microcystins observed in small headwater streams in the present study are a concern, given the potential consumption of aquatic life and water by terrestrial species, including humans . None of the microcystin concentrations we observed (3.2 µg/L maximum microcystin concentration) exceeded the World Health Organization moderate probability of acute adverse human health effects criterion for microcystins of 10 µg/L .…”
Section: Resultscontrasting
confidence: 58%
See 1 more Smart Citation
“…The persistent, measureable levels of microcystins observed in small headwater streams in the present study are a concern, given the potential consumption of aquatic life and water by terrestrial species, including humans . None of the microcystin concentrations we observed (3.2 µg/L maximum microcystin concentration) exceeded the World Health Organization moderate probability of acute adverse human health effects criterion for microcystins of 10 µg/L .…”
Section: Resultscontrasting
confidence: 58%
“…Microcystin-associated human illness has been documented in the United States by the Centers of Disease Control and Prevention [58], and microcystin-related human fatalities have been reported in other countries [40]. The persistent, measureable levels of microcystins observed in small headwater streams in the present study are a concern, given the potential consumption of aquatic life and water by terrestrial species, including humans [53,56,59,60]. None of the microcystin concentrations we observed (3.2 mg/L maximum microcystin concentration) exceeded the World Health Organization moderate probability of acute adverse human health effects criterion for microcystins of 10 mg/L [40].…”
Section: Potential Microcystin Environmental Health Effectsmentioning
confidence: 69%
“…Different concentrations of MCs from the same sample have been previously detected with different analysis methods (e.g., Gkelis et al, 2006;Hardy et al, 2015). Comparison of MC concentrations in different organisms is difficult due to the variety of methods employed, protein binding affinity, and differences in pharmacokinetics in different organisms (Adamovskỳ et al, 2007;Zhang et al, 2013b). Analysis methods may be more comparable if they have similar extraction efficiencies, but many studies do not report this critical information.…”
Section: Lc-ms/ms Gc-ms;mentioning
confidence: 99%
“…In recent study, Zhang et al (2013) studied the total protein content in plasma from six kinds of mammals and fish and purified albumin. They found that total plasma protein and albumin content in mammals were nearly two times and four times higher than that in fish, respectively.…”
Section: Results and Dicussionmentioning
confidence: 99%